Lines in the three-dimensional Bolyai-Lobachevskian hyperbolic geometry - GÁBOS, Zoltán; MESTER, Ágnes (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
The purpose of this paper is to describe the geodesics of the three- dimensional Bolyai-Lobachevskian hyperbolic space. We also determine the equation of the orthogonal surfaces and the scalar curvature of the surfaces of revolution. The metric applied is the Lobachevskian metric extended into three dimensions. During the analysis we use Cartesian and cylindrical coordinates. This article is a continuation of the paper [4]. Mathematics Subject Classification (2010): 53A35.